Parameter estimation of an electrochemical supercapacitor model - Drummond, R; Howey, D; Duncan, S (IEEE, 2017)
Parameter estimation of a supercapacitor model that uses PDEs to describe electrochemical physical phenomena is studied. The model parameters were identified from time domain charge/discharge data and also from frequency domain data in the form of electrical impedance spectroscopy at different open cell voltages. The identified physical model could fairly accurately simulate the experimental data, however, this accuracy was found to drop off at high frequencies. The performance of the physical model was compared to a second order circuit, with the two models having similar levels of accuracy. The circuit was found to be simpler to implement but, unlike the physical model, could not supply physical information about the internal state of the supercapacitor.